Pemanfaatan Media Sosial Untuk Promosi Pariwisata Dan Potensi Kearifan Lokal Di Kolam Alam Tilanga’ Kecamatan Makale Utara Kabupaten Tana Toraja - Yelvianti Tumba’ Makko’; Abedneigo Carter Rambulangi (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The aim of this research is to find out how to use social media as a suggestion for tourism promotion and local wisdom in the Tilanga Alam Pool, North Makale District, Tana Toraja Regency. This study uses a qualitative method. Qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people or actors who can be observed. Data collection procedures for observations were carried out using several methods, namely observation, interviews and documentation. The results obtained are in promoting tourism and the potential of local wisdom in the Tilanga' natural pool, North Makale District, Tana Toraja Regency, by utilizing creator content because the Tilanga' Natural Pool does not yet have its own media account to use, by utilizing creator content via Instagram and YouTube it can increase the number of tourists visiting from 2018-mid 2023 although the number is unstable.